Therapeutic Applications of Cysteamine and Cystamine in Neurodegenerative and Neuropsychiatric Diseases - Paul, Bindu D.; Snyder, Solomon H. (Frontiers in Neurology, 2019)
Current medications for neurodegenerative and neuropsychiatric diseases such as Alzheimer’s disease (AD), Huntington’s disease (HD), Parkinson’s disease (PD) and Schizophrenia mainly target disease symptoms. Thus, there is an urgent need to develop novel therapeutics that can delay, halt or reverse disease progression. AD, HD, PD and schizophrenia are characterized by elevated oxidative and nitrosative stress, which play a central role in pathogenesis. Clinical trials utilizing antioxidants to counter disease progression have largely been unsuccessful. Most antioxidants are relatively non-specific and do not adequately target neuroprotective pathways. Accordingly, a search for agents that restore redox balance as well as halt or reverse neuronal loss is underway. The small molecules, cysteamine, the decarboxylated derivative of the amino acid cysteine, and cystamine, the oxidized form of cysteamine respectively, mitigate oxidative stress and inflammation and upregulate neuroprotective pathways involving brain-derived neurotrophic factor (BDNF) and Nuclear factor erythroid 2-related factor 2 (Nrf2) signaling. Cysteamine can traverse the blood brain barrier, a desirable characteristic of drugs targeting neurodegeneration. This review addresses recent developments in the use of these aminothiols to counter neurodegeneration and neuropsychiatric deficits.